Pharmaceutical provision as a complex work of pharmacy stakeholders - Hubar, Myroslava; Sholoiko, Natalia (The Ukrainian Scientific Medical Youth Journal, 2025)
pharmaceutical provision plays a leading role in maintaining the proper level of public health and social security. From the perspective of a holistic approach, the pharmaceutical provision system is an integrated structure that combines the processes of manufacturing and circulation of medicines, as well as the implementation of pharmaceutical care and services. However an approach, that would characterize pharmaceutical provision as a complex work of its stakeholders and would describe the role of each of them, has not been formulated yet. The aim of the research was to characterize the approach according to which pharmaceutical provision is a complex work of stakeholders of the pharmacy field and to describe their roles in its context. For the stated purpose, we used content analysis, logical and system analyses. Printed and electronic open information sources, current legislation of Ukraine, and scientometric databases were the materials of our research. As a result of the data analysis, we identified the main stakeholders of pharmaceutical provision system – pharmacies, pharmaceutical manufacturers, wholesale pharmaceutical companies and the state. Pharmacies are a key link for proper functioning of pharmaceutical provision system because their employees are in direct contact with consumers of medicines and medical devices, thus providing pharmaceutical care and pharmaceutical services. It is obvious that the vast majority of medicines is industrially produced, so manufacturing pharmaceutical companies may be considered as flagships of pharmaceutical provision. Their activities promote the development of medicines, around which, in fact, the system of pharmaceutical provision revolves. The work of wholesale pharmaceutical companies creates and maintains supply chains, thereby ensuring continuity and the physical availability of medicines. Pharmaceutical logistics is quite specific with the highest level of responsibility and unconditional compliance with international standarts. The state implements pharmaceutical provision for the population through different mechanisms of organizational, economic, social, controlling, legal and educational nature. The generation and support of state authorized bodies and institutions, the approval of national and sectoral regulations help to clearly establish rules for the functioning of all participants in pharmaceutical provision, outline their responsibilities, duties, and rights, and protect consumers of medicines at the same time. And only the coordinated work of all stakeholders can ensure effective pharmaceutical provision to meet society's needs for its own safety and health.